因式分解9x^2(a-b)^3+4y^2(b-a)^3
3个回答
=(a-b)^3(9x^2-4y^2)
=(3x-2y)(3x+2y)(a-b)^3
相关问题
因式分解:① (x+y)^2-(3x-2y)^2 ②9(2a+3b)^2-25(3a-b)^2 ③a^3+4a^2b+4
因式分解:(1)(a+b)x2-(a+b);(2)9(a+b)2-4(a-b)2;(3)6xy2-9x2y-y3;(4)
因式分解.1:a^2b-6ab=9b2:y^3(x-2)=y(2-x)3:a^2-b^2-(a-b)^2 4:4a^2-
因式分解 16x^2y-16x^3-4xy^2 4ab^2-9a^2b-b^3 25(a-b)^2-9(a+b)^2 (
因式分解1.9(a+b)^2+12(a+b)+4 2.(a^3+4a^2+4a)÷(a^2+2a) 3.3(y-x)^2
因式分解:1、(x+y)-4(x+y)+3 2、 4a²-b²+6a-3b 3、 x²-2
因式分解:x²-y²-x+y=________ 因式分解:(a-b)²+2(a-b)-3
因式分解(1) 16-24(a+b)+9(a+b)^2 (2) (x-y)^2-4(x-y-1) (3)m(x-y)^2
因式分解(1)x2-9y2(2)2x(a-b)-(b-a)(3)x4-9x2(4)81x4-72x2y2+16y4.
因式分解:(1)2x(a-b)-(b-a)(2)3a2-27(3)-4a2x2+8ax-4(4)9(2a+3b)2-4(